Effects of muramyl dipeptide on superoxide anion release and on anti-microbial activity of human macrophages. - Wilson, C B (1982)
Exposure of human monocyte derived macrophages to muramyl dipeptide in vitro increased phorbol myristate acetate-stimulated O2- release by these cells; the activity of such macrophages against Toxoplasma gondii or against Staphylococcus aureus was not increased. The failure of muramyl dipeptide to enhance human macrophage anti-microbial activity correlated with the failure of muramyl dipeptide to enhance O2- release in response to phagocytic stimuli. These results and those previously published by others indicate that muramyl dipeptide may enhance release of certain inflammatory mediators (O2- and endogenous pyrogen) without enhancing the anti-microbial activity of human macrophages.